2015
DOI: 10.3390/ijms161025108
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Anti-Tumor Effects of Ozonated Water in Vivo

Abstract: Ozonated water is easier to handle than ozone gas. However, there have been no previous reports on the biological effects of ozonated water. We conducted a study on the safety of ozonated water and its anti-tumor effects using a tumor-bearing mouse model and normal controls. Local administration of ozonated water (208 mM) was not associated with any detrimental effects in normal tissues. On the other hand, local administration of ozonated water (20.8, 41.6, 104, or 208 mM) directly into the tumor tissue induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Regarding O 2 /O 3 therapy, evidence has been provided of the anti-cancer effect of local administration of ozonated water treatment in vitro and in vivo, in a mouse model of rectal cancer. The local treatment induced damages only in the tumor tissues by inducing necrosis without affecting normal tissues [ 43 ]. Moreover, the inhibitory effect of O 2 /O 3 treatment in two human neuroblastoma cell lines was analyzed [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding O 2 /O 3 therapy, evidence has been provided of the anti-cancer effect of local administration of ozonated water treatment in vitro and in vivo, in a mouse model of rectal cancer. The local treatment induced damages only in the tumor tissues by inducing necrosis without affecting normal tissues [ 43 ]. Moreover, the inhibitory effect of O 2 /O 3 treatment in two human neuroblastoma cell lines was analyzed [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ozonated water is the liquid form generated when ozone is dissolved in saline, which is much easier to handle than the gaseous form. The safety and direct antitumor effect of ozonated water have been previously described by us ( 3 ).…”
Section: Introductionmentioning
confidence: 74%
“…Another study in an animal model (tumor-bearing mouse model with rectal cancer) showed an antitumor effect of intratumor injection of ozonated water [ 31 ]. The effect was probably mediated by a local immunomodulation effect induced by ozone.…”
Section: Animal Modelsmentioning
confidence: 99%